Spin distribution of evaporation residue cross section within a stochastic approach - 杨宏伟 叶巍 (Chinese physics C, 2008)
The Langevin equation including particle emission was used to reproduce the recently measured spin distribution of evaporation residue cross sections in the reaction ^16O＋^184W at beam energies of 84, 92, 100, 108, 116 and 120 MeV. By comparing the theoretical calculations with the experimental data, the validity of the stochastic approach to dissipative fission is verified. Moreover, a pre-saddle nuclear viscosity coefficient of 5×10^21 s^-1 is extracted.